On the available names for the northern and eastern South American subspecies of Puma concolor (Linnaeus, 1771) (Mammalia: Felidae) and their type localities - Nascimento, F. O.; Garbino, G. S.t. (Zootaxa, 2013)
The puma, Puma concolor (Linnaeus, 1771), is one of the widest distributed mammals of the world, occurring historically from southwestern Canada to southern Argentina (Young and Goldman 1946, Macdonald et al., 2010). For this reason, more than 40 nominal forms were described for the species (Wozencraft, 2005). Recently, Culver et al. (2000), based on three mtDNA sequences and 10 microsatellite loci, defined six phylogeographic groupings of P. concolor, assigning six subspecific names to these groups. This taxonomic arrangement was followed in the mammalian taxonomic compendium edited by Wilson and Reeder (2005), although the subspecific name used for the eastern Brazilian subspecies was not the same (Wozencraft 2005).